Historical Analysis of the Concept of Nationalism in India and Allama Muhammad Iqbal: A Case of Muslim Identity in South Asia - Dr. Nazia Rahat; Dr. Rashida Qazi; Dr. Sohail Akhtar; Sajawal Qayyum; Madeeha Naz; Dilshad Noor (Al-Qanṭara, 2022)
This is an analytical study of Iqbal concept of Nationalism and Muslim identity in India. Allama Iqbal was a great Muslim mind of India and he provided a breath to the Muslims of India after their decline in 1857. The Colonial masters and Hindus tried to crush the Muslims not only but they wanted to demolish Muslim’s identity in India. Iqbal motivated the Muslims to be united as Millat being the followers of Islam and he preached Muslims are different nation due to a different religion Islam. He advised the Muslim of India to connect with one another as the branches are connected with a tree. Iqbal taught Muslims to be a nation for the political survival of the subcontinent. For this reason, Iqbal made individual and nation the subject of his philosophy and preferred the word nation for Muslims instead of Muslim nation. This paper primarily highlights Iqbal’s concept of Muslim Nationalism.